Static and Dynamic Cognitive Deficits in Childhood Preceding Adult Schizophrenia: A 30-Year Study - Reichenberg, Abraham (2010)
OBJECTIVE: Premorbid cognitive deficits in schizophrenia are well documented and have been interpreted as supporting a neurodevelopmental etiological model. The authors investigated the following three unresolved questions about premorbid cognitive deficits: What is their developmental course? Do all premorbid cognitive deficits follow the same course? Are premorbid cognitive deficits specific to schizophrenia or shared by other psychiatric disorders? METHODS: Participants were members of a representative cohort of 1,037 males and females born between 1972 and 1973 in Dunedin, New Zealand. Cohort members underwent follow-up evaluations at specific intervals from age 3 to 32 years, with a 96% retention rate. Cognitive development was analyzed and compared in children who later developed schizophrenia or recurrent depression as well as in healthy comparison subjects. RESULTS: Children who developed adult schizophrenia exhibited developmental deficits (i.e., static cognitive impairments that emerge early and remain stable) on tests indexing verbal and visual knowledge acquisition, reasoning, and conceptualization. In addition, these children exhibited developmental lags (i.e., growth that is slower relative to healthy comparison subjects) on tests indexing processing speed, attention, visual-spatial problem solving ability, and working memory. These two premorbid cognitive patterns were not observed in children who later developed recurrent depression. CONCLUSIONS: These findings suggest that the origins of schizophrenia include two interrelated developmental processes evident from childhood to early adolescence (ages 7–13 years). Children who will grow up to develop adult schizophrenia enter primary school struggling with verbal reasoning and lag further behind their peers in working memory, attention, and processing speed as they get older.